2020
DOI: 10.1002/cpp.2514
|View full text |Cite
|
Sign up to set email alerts
|

Distress tolerance and special alcohol metacognitions behave differently in the association of negative affect with alcohol‐related patterns in men with problematic alcohol use in the abstinence phase

Abstract: Negative affect may be related to alcohol‐related patterns (e.g., craving and problematic alcohol use). Distress intolerance and positive and negative alcohol‐related metacognitions may be underlying mechanisms in this link. This study aimed to evaluate the effect of negative affect including depressive, anxious, and stress symptoms on alcohol craving and problematic alcohol use via the paths of distress tolerance and both positive and negative alcohol‐related metacognitions. Three hundred men with problematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Consistent with our hypothesis, the study nding reveals a signi cantly inverse link of the dependence severity with stress tolerance levels and facing negative emotions; however, this nding explains the small variance (only 6%). A similar observation has been reported and appears to be mediated by internal drinking motives, coping motives, cognitive schema, distinct alcohol metacognitions, and depressive symptoms [39], [14], [40],[16], [41], [17] . Hayes argued that it is feasible for a predictor (X) to impact an outcome (Y) variable indirectly via a mediator (M) even if the overall effect of X on Y cannot be proven to be more than zero [42] .…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with our hypothesis, the study nding reveals a signi cantly inverse link of the dependence severity with stress tolerance levels and facing negative emotions; however, this nding explains the small variance (only 6%). A similar observation has been reported and appears to be mediated by internal drinking motives, coping motives, cognitive schema, distinct alcohol metacognitions, and depressive symptoms [39], [14], [40],[16], [41], [17] . Hayes argued that it is feasible for a predictor (X) to impact an outcome (Y) variable indirectly via a mediator (M) even if the overall effect of X on Y cannot be proven to be more than zero [42] .…”
Section: Discussionsupporting
confidence: 79%
“…Higher scores indicate more severe levels of harmful alcohol use. The AUDIT has good internal reliability in individuals with problematic alcohol use (Khosravani et al, 2021). In the current study, the Cronbach alpha was 0.90, indicating excellent reliability.…”
Section: Methodsmentioning
confidence: 99%
“…The association between low distress tolerance and poor emotion regulation was demonstrated in the context of alcohol drinking in non-clinical samples. For example, a study conducted among men with problematic alcohol use found that distress intolerance impacted the association between negative affect and craving (13). In a study by Howell and colleagues (6) distress tolerance was related to coping motives for alcohol use in a community sample of young adults.…”
Section: Introductionmentioning
confidence: 99%